2004
DOI: 10.1143/jjap.43.8223
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Excess Si Emitted from Si-oxide/Si Interfaces

Abstract: The excess Si emitted from the Si-oxide/Si interface is studied using the first-principles calculations. It is shown that the excess Si can have many (meta-) stable positions around the interface. In addition, some positions in the oxide do not have any dangling bonds or floating bonds in contrast to those in the bulk crystalline Si. The results indicate that the emitted Si can be located in the oxide layer but they do not necessarily cause charge traps in the oxide. The emitted Si atoms are thought to just be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…According to Kageshima etal., the Si emission is a major cause for the missing Si [20][21][22][23][24][25][26][27][28][29]. It is * Corresponding author: efukuda@cies.tohoku.ac.jp also reported that the amount of Si emission is larger in the pillar-shape Si oxidation than in the planar Si oxidation, where the emission becomes more prominent as the Si pillar diameter becomes smaller.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kageshima etal., the Si emission is a major cause for the missing Si [20][21][22][23][24][25][26][27][28][29]. It is * Corresponding author: efukuda@cies.tohoku.ac.jp also reported that the amount of Si emission is larger in the pillar-shape Si oxidation than in the planar Si oxidation, where the emission becomes more prominent as the Si pillar diameter becomes smaller.…”
Section: Introductionmentioning
confidence: 99%
“…This happens because of the segregation of B atoms into the surface oxide layer during thermal oxidation . The normal oxidation at high temperature of 900 °C introduces Si self-interstitials into crystalline Si core of SiNWs. These two effects, high temperature annealing and introduction of defects, enhance the segregation of B atoms into the surface oxide layer. Figure c shows the comparison between the normal oxidation and the ozone oxidation at 600 °C in addition to the data obtained for the normal oxidation at 900 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this, enhanced B diffusion during oxidation is a possible reason for the fast segregation of B atoms. It is well-known that dopant diffusion is enhanced under an oxidizing ambient. This phenomenon is called transient enhanced diffusion (TED) or oxidation-enhanced diffusion (OED). Silicon self-interstitials are generated at the Si/SiO 2 interface during oxidation. B atoms are generally accepted to diffuse in Si crystal predominantly by a kick-out mechanism that involves Si self-interstitials . A Si interstitial kicks out the substitutional B atom to an interstitial position where it can diffuse easily.…”
mentioning
confidence: 99%
“…[27][28][29][30][31] Silicon self-interstitials are generated at the Si/SiO 2 interface during oxidation. [27][28][29][30][31][32][33] B atoms are generally accepted to diffuse in Si crystal predominantly by a kick-out mechanism that involves Si self-interstitials. 34 A Si interstitial kicks out the substitutional B atom to an interstitial position where it can diffuse easily.…”
mentioning
confidence: 99%